Avaliação das atividades da metformina em modelos experimentais de dores nociceptiva, inflamatória e neuropática e inflamação - Paulo Sergio de Almeida Augusto (2016)
Metformin is an oral hypoglycemic drug widely used to treat patients with type 2 diabetes. Although some studies have demonstrated that metformin exhibits anti-inflammatory activity, probably associated with inhibition of TNF-, IL-6, IL1, IL-17 and NO production, little is known about its effects in experimental models of pain. Thus, the present study aimed to evaluate the activity of metformin in experimental models of nociceptive, inflammatory and neuropathic pain in mice, as well as the mechanisms mediating this activity. The study may contribute to a greater knowledge of metformin pharmacological profile and provide support to its repositioning in the treatment of patients with painful and inflammatory diseases. Metformin (250, 500 or 1000 mg/kg, p.o, -1 h) inhibited the nociceptive response induced by heat in hot plate (50 oC) and formaldehyde (1%, 20 L, s.c.). Metformin also inhibited the mechanical allodynia and paw edema induced by carrageenan (600 g, 30 L, i.pl.), as well as the pleurisy induced by this stimuli (200 g, intrapleural). In the models of mechanical allodynia and paw edema induced by carrageenan, metformin also exhibited activity when administered after induction of the inflammation. Metformin also exhibited activity in the model of neuropathic pain induced by chronic constriction injury. Treatment with metformin (1000 mg/kg) during three days, from the 7th day after the constriction of the sciatic nerve, reverted the mechanical allodynia without inducing tolerance. Metformin did not change the time mice spent on the rota-rod, indicating that the inhibition of the nociceptive behavior results from an intrinsic antinociceptive activity. Although previous studies have suggested that activation of AMPK and interaction with imidazolinic receptors, as well as reduced production of inflammatory mediators, may mediate the antinociceptive activity of metformin, the present study indicates that other mechanisms may be involved. The activity of metformin in the model of nociceptive pain induced by heat was attenuated by previous administration of naltrexone (5 or 10 mg/kg, i.p.) or cyproheptadine (5 or 10 mg/kg, p.o). In addition, in the model of inflammatory pain, the activity of metformin was abolished by previous administration of glibenclamide (20 ou 40 mg/kg, p.o). In conclusion, the results demonstrate the activity of metformin in models of nociceptive, inflammatory and neuropathic pain, as well as in models of inflammatory edema and pleurisy. In addition, the results indicate that the activity of metformin may be mediated by activation of opioidergic and serotoninergic pathways, as well as ATP-sensitive potassium channels. The demonstration of the activity of metformin in various pain and inflammation models may stimulate the conduction of studies aiming its repositioning in the treatment of patients with painful and inflammatory disorders.